A new Eocyzicus (Branchiopoda: Spinicaudata) from Taiwan, with a review of the genus - Rogers, D. Christopher; Chang, Tso Chia; Wang, Yung-Chuan (Zootaxa, 2017)
We present the first record of Eocyzicus from Taiwan. Eocyzicus taiwanensis n. sp. can be distinguished from all other Eocyzicus species by the form of the claspers, the telson and the cercopods. This new species is so far known only from the type locality, which is a series of flood irrigated garlic fields in the Tainan District. The genus is reviewed superficially and revised conservatively. We recognize 19 Eocyzicus species, three nomina dubia and inquirendae, and 71 synonyms.